2020
DOI: 10.1016/j.jtho.2020.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel CD74-NRG2α Fusion From Comprehensive Profiling of Lung Adenocarcinoma in Japanese Never or Light Smokers

Abstract: Introduction: Studies are yet to characterize the differences in molecular profiles of lung adenocarcinoma (LUAD) among divergent ethnic groups. Herein, we conducted comprehensive molecular profiling of LUAD in never or light smokers from Asia to discover novel targetable mutations and prognostic biomarkers of this distinct disease entity. Methods: We analyzed 996 cases of Japanese LUAD and performed whole-exome sequencing and RNA-seq in 125 cases of Japanese LUAD negative for the driver oncogenes defined by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 47 publications
4
54
2
Order By: Relevance
“…In addition to METex14 described above, EGFR , ALK/ROS1 and KRAS‐ altered adenocarcinomas frequently exhibited lepidic, acinar and mucinous histology, respectively, in agreement with previous studies 14‐16,29 . Additionally, ERBB2 ‐mutated LAD, which is over‐represented in young adults, 20 was associated with the micropapillary pattern. In contrast, distinct histological features were not detected in RET , BRAF and MAP2K1 ‐altered LAD, although both BRAF and MAP2K1 ‐mutated LAD frequently exhibited AIS or minimally invasive adenocarcinoma.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to METex14 described above, EGFR , ALK/ROS1 and KRAS‐ altered adenocarcinomas frequently exhibited lepidic, acinar and mucinous histology, respectively, in agreement with previous studies 14‐16,29 . Additionally, ERBB2 ‐mutated LAD, which is over‐represented in young adults, 20 was associated with the micropapillary pattern. In contrast, distinct histological features were not detected in RET , BRAF and MAP2K1 ‐altered LAD, although both BRAF and MAP2K1 ‐mutated LAD frequently exhibited AIS or minimally invasive adenocarcinoma.…”
Section: Discussionsupporting
confidence: 90%
“…Our archives included data for 996 primary LADs from 920 patients, and comprised details on oncogene alterations such as mutant EGFR , KRAS , ERBB2 , BRAF , MAP2K1 or rearranged ALK , ROS1 , RET , NRG1 or METex14 (Figure ). We previously detected these alterations using the peptide nucleic acid‐locked nucleic acid polymerase chain reaction (PCR) clamp method, break‐apart fluorescence in‐situ hybridisation (FISH), whole‐exome sequencing and RNA sequencing; 20 among 996 LADs, 679 cases had mitogenic alterations. A case with CD74–NRG2 fusion was excluded in this study, and we examined the remaining 678 LADs.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, rare actionable alterations, such as NRG2 fusions, would be missed. 34 In addition, for common alterations, only "hotspot exons" were sequenced, and thus rare fusion variants involving ALK, ROS1, and RET may have been undetected. However, WTS can detect all coding regions to comprehensively explore known and unknown fusions, which may identify rare alterations that offer an optimal treatment option for patients with non-small cell lung neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Some experimental models have investigated MEK inhibitors for MAP2K1 in-frame deletions [ 15 , 16 , 26 , 27 ]. Gao et al reported in vitro experiments where Classes 1 and 2 MAP2K1 mutants were effectively inhibited by allosteric MEK1 inhibitors, while Class 3 mutants, represented by in-frame deletions, were resistant [ 16 ].…”
Section: Discussionmentioning
confidence: 99%